A 0-1 quadratic programme for the case of missing data in regression. (1st January 2014) - Smith, Brian K.; Chimka, Justin R.; Nachtmann, Heather
Multivariate statistical analysis techniques including regression analysis compose a popular toolset for analysing survey data, but the techniques require a complete dataset with no missing values. Unfortunately, most survey datasets contain missing values. These missing values must be resolved in some manner before regression analysis can take place. We present a quadratic programming methodology for eliminating non-responses from a survey dataset.